Effect of pre-heating resin composite and light-curing units on monomer conversion - Saade, E. G.; Bandéca, M. C.; Saade, J. L.; Rossato, D. M.; Rastelli, Alessandra Nara de Souza [UNESP]; Bagnato, V. S.; Porto-Neto, S. T. (Pleiades Publishing, 2010)
The purpose of this study was to evaluate the effect of pre-heating resin composite photo-cured with light-curing units (LCU) by FT-IR. Twenty specimens were made in a metallic mold (4 mm diameter × 2 mm thick) from composite resin-Tetric Ceram® (Ivoclar/Vivadent) at room temperature (25°C) and pre-heated to 37, 54, and 60°C. The specimens were cured with halogen curing light (QTH) and light emitted by diodes (LED) during 40 s. Then, the specimens were pulverized, pressed with KBr and analyzed with FT-IR. The data were submitted to statistical analysis of variance and Kruskal-Wallis test. Study data showed no statistically significant difference to the degree of conversion for the different light curing units (QTH and LED) (p > 0.05). With the increase of temperature there was significant increase in the degree of conversion (p < 0.05). In this study were not found evidence that the light curing unit and temperature influenced the degree of conversion. © 2010 Pleiades Publishing, Ltd.
Keywords: Composite resins; Degree of conversion; Halogen curing; Kruskal; Light-curing units; Metallic mold; Monomer conversions; Resin composites; Room temperature; Statistical analysis; Statistically significant difference; Dental composites; Heating; Light emitting diodes; Regression analysis; Resins; Curing